“Cold turkey meds again”: Access to community HIV/AIDS services during public health emergencies - Darby Whittaker; Erynn Monette; Miesha Polintan; Elijah Bisung (Wellbeing, Space and Society)
This paper works to explore the experiences of people living with HIV (PLWH) in relation to the closure of AIDS Service Organizations (ASOs) in Ontario, Canada, during the COVID-19 pandemic and offers recommendations on how to ensure a continuum of care for PLWH during public health emergencies like COVID-19. Semi-structured in-depth interviews were conducted with PLWH (n = 8) and ASO service providers (n = 8). Participants discussed their experiences with HIV services throughout the pandemic. Of the PLWH interviewed, individuals shared experiences of worsening mental health outcomes, difficulties accessing resources, disruption in medical care, and increased feelings of isolation. ASO service providers identified changes in their functions, increased barriers in service provision, and staff fatigue as challenges to their work. The results of this study demonstrate the need for reimagining HIV/AIDS and other service provisions during pandemics to ensure that resources remain accessible for PLWH and other marginalized populations. Essential ASO services to maintain a continuum of care during pandemic circumstances include prioritizing mental health supports, regular access to nutritious food, clothing, and financial support, and consistent check-ins between clients and service providers.